Smart fertilizers for efficient nutrient management - Biswal, Bisworanjita; Kashyap, Suryakanta; Ram, Hardev; Kumar, Rakesh (Indian Farming, 2020)
Application of smart fertilizers based on slow-/controlled-release and/or carrier delivery systems along with smart fertilization techniques has the potential to achieve efficient nutrient management to meet the target productivity, reduce environmental stress and attain sustainable development goals. Zeolites, polymers and agricultural wastes that act as carrier for nutrients and biofertiliser can be suitable material for smart fertilizer production. The main hindrance in expansion of smart fertilizer is low-installed production capacity. Future research should explore its suitability, feasibility and user friendly aspect of smart fertilizers. Innovative fertilizers from naturally available materials would ensure sustainability of agricultural production system.